Crypto Assets as Dowry in Marriage According to Islamic Law in Indonesia - Kirana, Anggun; Mahmudah, Masrifatun; Ali, Muhammad (Journal of Transcendental Law, 2023)
Nowadays, crypto assets are increasingly showing their existence, not only as digital assets but can also be used as dowries in marriage. However, the use of crypto assets as dowry does not yet have a legal basis in the Marriage Law or its amendments. Instead, it is determined that the validity of marriage is returned to the religious law of each prospective bride and groom. The focus of the purpose of this research is to analyze the law of crypto assets as a dowry in marriage from the perspective of Islamic law in Indonesia. This research is a type of normative legal research using the statute approach method. The legal materials used are primary and secondary legal materials. Data collection techniques are carried out through literature studies by tracing, collecting, researching, and reviewing or analyzing legal materials. The data obtained is then analyzed using qualitative analysis. The results show that the provisions regarding dowry in marriage according to Islamic Law are specifically regulated in the Compilation of Islamic Law, but there are no provisions regarding the conditions under which something can be used as dowry. In the legal context, crypto assets as a dowry in marriage according to Islamic law in Indonesia, based on the conditions of dowry outlined by Shaykh Abdurrahman Al-Juzairi, are invalid because crypto assets do not meet some of the requirements of dowry, namely valuable property, holy and halal goods, and known types and characteristics.